RELASI SEMANTIK BAHASA BANJAR DIALEK HULU - M. Ridha Anwari Muhammad Yunus (Universitas Lambung Mangkurat, 2020)
Abstract Semantic Relations of the Hulu Banjar Dialect Language. Semantic relations are semantic relations that exist between one language unit with another language unit. The formulation of the problem in this research is how is the semantic relation of the words synonym, antonym, hominim, hyponym, and polysemy of the Banjar dialect language upstream? This study aims to describe the semantic relations of words in BBDH so that they can be known by their speakers. The research method used in this research is descriptive method. The results of this study are the forms of semantic relations found in the communication patterns of the Banjar upstream dialect community in the form of Synonyms, Antonyms, Homonyms, Polisemi, and Hyponyms. Key words: semantic relations, banjar language, hulu dialect Abstrak Relasi Semantik Bahasa Banjar Dialek Hulu. Relasi semantik adalah hubungan semantik yang terdapat antara satuan bahasa yang satu dengan satuan bahasa yang lainnya. Rumusan masalah dalam penelitian ini ialah bagaimanakah relasi semantik kata sinonim, antonim, hominim, hiponim, dan polisemi bahasa Banjar dialek hulu? Penelitian ini bertujuan untuk mendeskripsikan relasi semantik kata dalam BBDH agar dapat diketahui oleh penuturnya. Metode penelitian yang digunakan dalam penelitian ini adalah motode deskriptif. Hasil penelitian ini ialah bentuk-bentuk relasi semantik yang ditemukan dalam pola komunikasi masyarakat Banjar dialek hulu berupa Sinonim, Antonim, Homonim, Polisemi, dan Hiponim. Kata-kata kunci: relasi semantik, bahasa banjar, dialek hulu